Ovarian response to 150 µg corifollitropin alfa in a GnRH-antagonist multiple-dose protocol: a prospective cohort study. Issue 5 (May 2017) - Lerman, Tamara; Depenbusch, Marion; Schultze-Mosgau, Askan; von Otte, Soeren; Scheinhardt, Markus; Koenig, Inke; Kamischke, Axel; Macek, Milan; Schwennicke, Arne; Segerer, Sabine; Griesinger, Georg
Abstract: The incidence of low (<6 oocytes) and high (>18 oocytes) ovarian response to 150 µg corifollitropin alfa in relation to anti-Müllerian hormone (AMH) and other biomarkers was studied in a multi-centre ( n = 5), multi-national, prospective, investigator-initiated, observational cohort study. Infertile women ( n = 212), body weight >60 kg, underwent controlled ovarian stimulation in a gonadotrophin-releasing hormone-antagonist multiple-dose protocol. Demographic, sonographic and endocrine parameters were prospectively assessed on cycle day 2 or 3 of a spontaneous menstruation before the administration of 150 µg corifollitropin alfa. Serum AMH showed the best correlation with the number of oocytes obtained among all predictor variables. In receiver-operating characteristic analysis, AMH at a threshold of 0.91 ng/ml showed a sensitivity of 82.4%, specificity of 82.4%, positive predictive value 52.9%and negative predictive value 95.1% for predicting low response (area under the curve [AUC], 95% CI; P -value: 0.853, 0.769–0.936; <0.0001). For predicting high response, the optimal threshold for AMH was 2.58 ng/ml, relating to a sensitivity of 80.0%, specificity 82.1%, positive predictive value 42.5% and negative predictive value 96.1% (AUC, 95% CI; P -value: 0.871, 0.787–0.955; <0.0001). In conclusion, patients with serum AMH concentrations between approximately 0.9 and 2.6 ng/ml were unlikely to show extremes of response.